Desafios e alternativas financeiras em universidade pública brasileira: um estudo sobre o crowdfunding - Gomes, Ana Luzia Chavez (2021)
Access to information is a necessity in an increasingly technological society, and it is up to the university, among others, to seek to facilitate access and dissemination of information, contributing to improving the quality of life. Thus, it is necessary that the public communication process of science is revisited and adapted to the new demands of society. Science, Technology and Society is an area that is concerned with the social issues and controversies of science and technology and their possible consequences, unfolding and impacts. In this context, crowdfunding emerges, which in practice is one of the forms of collective financing, carried out through campaigns that are available on specialized websites, whose intention is to allow greater engagement, which can lead society to get involved in the process of doing science. This thesis is based on the assumption that crowdfunding is a phenomenon that can be adapted to the reality of the Brazilian public university that has suffered severe impacts caused by neoliberal political agendas, which jeopardize its financial sustainability. To this end, we used the bibliographic review to understand the state of the art of the crowdfunding theme and correlating it with the practical experience of practical campaigns to understand its possibility of application within universities. In the end, we understand that it is feasible and that there are some aspects that need to be further explored adapted to the Brazilian reality, since most of the examples of crowdfunding that we found applied to universities were of foreign origin.